First record of the blacktip reef shark Carcharhinus melanopterus (Carcharhiniformes: Carcharhinidae) from the Tropical Eastern Pacific - López-Garro, Andrés; Zanella, Ilena; Golfín-Duarte, Geiner; Pérez-Montero, Maikel (Revista de Biología Tropical, 2012)
The blacktip reef shark Carcharhinus melanopterus, is one of the most common Indo-Pacific reef sharks. On April 29, 2012, a juvenile male blacktip reef shark measuring 89 cm total length (TL), was incidentally caught during a research expedition in Chatham Bay, Isla del Coco National Park, Costa Rica, located in the Tropical Eastern Pacific. This is the first record of the species from Isla del Coco National Park, Costa Rica, and from the Tropical Eastern Pacific. Citation: López-Garro, A., I. Zanella, G. Golfín-Duarte & M. Pérez-Montero. 2012. First record of the blacktip reef shark Carcharhinus melanopterus (Carcharhiniformes: Carcharhinidae) from the Eastern Tropical Pacific. Rev. Biol. Trop. 60 (Suppl. 3): 275-278. Epub 2012 Dec 01.